2022
DOI: 10.1038/s41377-022-00985-4
|View full text |Cite
|
Sign up to set email alerts
|

InGaN micro-light-emitting diodes monolithically grown on Si: achieving ultra-stable operation through polarization and strain engineering

Abstract: Micro or submicron scale light-emitting diodes (µLEDs) have been extensively studied recently as the next-generation display technology. It is desired that µLEDs exhibit high stability and efficiency, submicron pixel size, and potential monolithic integration with Si-based complementary metal-oxide-semiconductor (CMOS) electronics. Achieving such µLEDs, however, has remained a daunting challenge. The polar nature of III-nitrides causes severe wavelength/color instability with varying carrier concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…As indicated in Fig. 4(b), Wu et al designed and fabricated green InGaN/GaN nanowire LEDs on Si through a bottom-up selective area epitaxy process [28]. In this work, they also applied an AlGaN/GaN shell surrounding the MQW with a negative Al composition gradient along c-axis to suppress quantum-confined Stark effect (QCSE).…”
Section: High-resolution Micro-ledmentioning
confidence: 99%
“…As indicated in Fig. 4(b), Wu et al designed and fabricated green InGaN/GaN nanowire LEDs on Si through a bottom-up selective area epitaxy process [28]. In this work, they also applied an AlGaN/GaN shell surrounding the MQW with a negative Al composition gradient along c-axis to suppress quantum-confined Stark effect (QCSE).…”
Section: High-resolution Micro-ledmentioning
confidence: 99%
“…When the current density rises from 0.1 to 1 kA/cm 2 , the EL peak wavelength of the GaN-on-Si green micro-LED shifts from 524.3 to 495.6 nm due to the quantum confinement Stark effect (QCSE) caused by the piezoelectric field in the MQWs. The severe wavelength blue shift is expected to be mitigated by special designs of quantum well structures or the introduction of the optical microcavity. ,, At the same time, the FWHM of the micro-LED will also increase from 20.2 to 44 nm, when the operating current density increases from 0.1 to 1 kA/cm 2 . It has been reported that green LEDs with EL peak wavelengths in the range of 525–535 nm and FWHM not exceeding 25 nm can meet the requirements of the Rec.…”
Section: Resultsmentioning
confidence: 99%
“…When The severe wavelength blue shift is expected to be mitigated by special designs of quantum well structures or the introduction of the optical microcavity. 8,23,24 At the same time, the FWHM of the micro-LED will also increase from 20.2 to 44 nm, when the operating current density increases from 0.1 to 1 kA/cm 2 . It has been reported that green LEDs with EL peak wavelengths in the range of 525−535 nm and FWHM not exceeding 25 nm can meet the requirements of the Rec.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14–21 Therefore, 1D superlattice micro/nanostructures can function as ideal building blocks for developing easily manufactured, miniaturized and integrated electronics and photonic devices. 22–26…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Therefore, 1D superlattice micro/nanostructures can function as ideal building blocks for developing easily manufactured, miniaturized and integrated electronics and photonic devices. [22][23][24][25][26] For the past few years, several cleverly-designed thermal evaporation schemes have been proposed to prepare 1D semiconductor superlattice micro/nanowires, with segmented structures that could be modulated along the axial direction longitudinally. 9,11,27 This type of periodic composition of 1D superlattice crystals has aroused wide public interest due to the intriguing electronic and optical transport properties.…”
Section: Introductionmentioning
confidence: 99%